The Involvement of the Catholic Laity in the Promotion of Peace - Lóránd Ujházi (Religions)
In accordance with their constitutional prerogatives, members of the Church engage in activities that align with their designated roles and responsibilities. A review of both the history of the Church and the documents in force reveals that the Church, in its broadest sense, is concerned with the promotion of peace. Such areas are, by definition, those which fall within the purview of laypeople. The Second Vatican Council accorded particular attention to the promotion of social justice and peace, as well as to the apostolate of lay faithful. Consequently, the two areas were brought into contact and underwent further development. This paper presents the historical trajectory that has culminated in the most comprehensive positioning of the laity in the promotion of social justice, elucidating the legal distinctions pertaining to the most prevalent methods through which they can promote peace.